Commodity prices: how important are real and nominal shocks? - Bloch, Harry; Fraser, Patricia; MacDonald, Garry (Taylor & Francis, 2012)
We consider the response of both nominal and real commodity prices on world markets to real and nominal shocks by hypothesizing that nominal shocks can permanently affect nominal commodity prices, but can have only temporary effects on real commodity prices. Real shocks, in contrast, can have permanent as well as temporary effects on both nominal and real commodity prices. When nominal and real shocks are decomposed in this manner, real shocks are found to be of much greater importance to the observed movements in commodity prices. We use the Blanchard and Quah (BQ, 1989) decomposition to obtain the permanent and temporary components of the real commodity price series and relate this to the rate of growth of world industrial production as an indicator of business cycle movements. The results suggest that the impact of the business cycle is self-stabilizing in that there is an initial positive effect on growth in commodity prices followed by a fully offsetting negative effect.